Analysis of the role of polyphosphate kinase 1 in the physiology of Mycobacterium smegmatis and Mycobacterium tuberculosis as a promising drug target for the treatment of tuberculosis - Robert, Nnenna (Rhodes University, 2026)
Embargo applied. Embargo period to expire in October of 2027.
Keywords: Uncatalogued